Underrecovery and overtraining - Kellmann, M. (Olympic & Paralympic Coach, 2003)
Underrecovery and overtraining: Different concepts — similar impact? This question can clearly be answered with a yes and a no. Yes, they have the same impact—performance declines; No, they are not similar—underrecovery is the precursor/cause of overtraining. Consequently, the key to prevent overtraining is an active and proactive enhancement of recovery. Coaches and athletes need to be educated about the importance of optimal recovery and its impact on performance. When athletes understand that a weekend without training is part of the planned training schedule, which implies that they should not train on their own or go for a heavy bike ride with friends, they take a huge step toward adequate recovery. In addition, the multilevel concept of stress and recovery emphasizes that physical training is just one part of athletes` lives. Emotional worries outside of the training environment may disturb the recovery process as well. Consequently, athletes` self-initiated activities and coaches` knowledge about individual preferences for recovery strategies are important elements to avoid overtraining and subsequent underperformance.